2010
DOI: 10.1007/s10689-010-9393-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a large rearrangement in CYLD as a cause of familial cylindromatosis

Abstract: Pathogenic mutations in CYLD can be identified in patients affected with Brooke-Spiegler syndrome, (Familial) Cylindromatosis or multiple familial trichoepithelioma. To date, only technologies which are able to identify small point mutations in CYLD, such as sequence and WAVE analysis, were used. Here we describe the identification of a larger rearrangement identified by Quantitative PCR analysis of CYLD, indicating that a combination of these technologies is necessary when searching for pathogenic mutations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 23 publications
(29 reference statements)
0
28
0
Order By: Relevance
“…The distribution of nonsense mutations is also unequal in the CYLD gene (Figure 3). One third of the nonsense mutations occur within the region spanning exons 9-11 [Sima et al, 2010;Bignell et al, 2000;Bowen et al, 2005;Grossmann et al, 2013;Linos et al, 2011;Lv et al, 2008;Kacerovska et al, 2013;Saggar et al, 2008;Van den Ouweland et al, 2011;Kazakov et al, 2009;Almeida et al, 2008], while the majority (72%) are located within the region spanning exons 12-20 [Sima et al, 2010;Bignell et al, 2000;Zhang et al, 2004;Young et al, 2006;Oranje et al, 2008;Bowen et al, 2005;Grossmann et al, 2013;Oiso et al, 2004;Kazakov et al, 2009;Nagy et al, 2013;Nagy et al, 2012;Zheng et al, 2004;Chen et al, 2011;Almeida et al, 2008]. This latter region does not seem to contain a further mutational hotspot.…”
Section: Variants Of the Cyld Genementioning
confidence: 99%
See 3 more Smart Citations
“…The distribution of nonsense mutations is also unequal in the CYLD gene (Figure 3). One third of the nonsense mutations occur within the region spanning exons 9-11 [Sima et al, 2010;Bignell et al, 2000;Bowen et al, 2005;Grossmann et al, 2013;Linos et al, 2011;Lv et al, 2008;Kacerovska et al, 2013;Saggar et al, 2008;Van den Ouweland et al, 2011;Kazakov et al, 2009;Almeida et al, 2008], while the majority (72%) are located within the region spanning exons 12-20 [Sima et al, 2010;Bignell et al, 2000;Zhang et al, 2004;Young et al, 2006;Oranje et al, 2008;Bowen et al, 2005;Grossmann et al, 2013;Oiso et al, 2004;Kazakov et al, 2009;Nagy et al, 2013;Nagy et al, 2012;Zheng et al, 2004;Chen et al, 2011;Almeida et al, 2008]. This latter region does not seem to contain a further mutational hotspot.…”
Section: Variants Of the Cyld Genementioning
confidence: 99%
“…It is of interest to note that 25% of the identified nonsense mutations 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 9 affect glutamine amino acid residues within the CYLD protein, replacing them with stop codons [Sima et al, 2010;Bignell et al, 2000;Grossmann et al, 2013;Zheng et al, 2004;Chen et al, 2011;Almeida et al, 2008]. Nearly half of the nonsense mutations (40%) are recurrent [Sima et al, 2010;Bignell et al, 2000;Oranje et al, 2008;Bowen et al, 2005;Grossmann et al, 2013;Linos et al, 2011;Lv et al, 2008;Kacerovska et al, 2013;Saggar et al, 2008;Van den Ouweland et al, 2011;Oiso et al, 2004;Zhang et al, 2006;Kazakov et al, 2009;…”
Section: Variants Of the Cyld Genementioning
confidence: 99%
See 2 more Smart Citations
“…Gross rearrangements and chromosomal deletions are also potential factors. van den Ouweland et al (2011) identified a gross chromosomal rearrangement spanning approximately 5 kb involving the CYLD gene in a patient with familial cylindromatosis. Somatic mutation may also be important.…”
Section: Discussionmentioning
confidence: 99%